Profil Klinikopatologi Endometrioid Endometrial Carcinoma di RSUD Dr. Saiful Anwar Tahun 2022-2024 - Amelinda Natania Nurasih; Ihda Kusuma; Arif Arif (RSUD Dr. Saiful Anwar Province of East Java, 2026)
Background: Endometrial carcinoma holds the second highest incidence among gynecologic malignancies after cervical cancer, with increasing incidence and mortality globally. While it predominantly affects postmenopausal women, its incidence is steadily rising among premenopausal women. As the most prevalent subtype, endometrioid endometrial carcinoma (EEC) is closely linked to extended periods of unopposed estrogen stimulation. Obesity, type 2 diabetes, and nulliparity are also recognized as contributing risk factors. Aim: To describe the clinicopathological profile of EEC at Dr. Saiful Anwar General Hospital. Methods: This study employed a descriptive retrospective design based on secondary data obtained from medical records and histopathology reports. Inclusion criteria were patients diagnosed with EEC through hysterectomy specimens. Results: EEC cases increased over the past three years, with a 48% surge in 2024. Most patients were aged 51–60 years (mean age: 56.5) and showed deep myometrial invasion (≥½ thickness, 71.43%). The most common histological findings were FIGO grade 1 (45.23%) and stage IB (33.33%). Reproductive risk factors included postmenopausal status (63.3%), premenopausal status (36.67%), and nulliparity (23.3%). Among the patients, 18.33% had a history of diabetes mellitus, and 48.33% were obese (mean BMI: 27.83 kg/m²). Conclusion: There is a consistent upward trend in EEC incidence, with most patients diagnosed at an early stage and grade. An increasing proportion of cases is observed among obese and premenopausal women, with the youngest patient aged 29. Early detection and risk-based preventive strategies are essential to reduce EEC incidence and mortality.